Real time imaging of strain fields induced by the ferrite-to-austenite transformation in high purity iron. (September 2020) - Bruzy, Nicolas; Coret, Michel; Huneau, Bertrand; Stainier, Laurent; Denoual, Christophe; Mondon, Marilyne; Kermouche, Guillaume
Graphical abstract: Abstract: During the ferrite-to-austenite transformation, the accommodation of the volume misfit between ferrite and austenite induces strain localization in both phases. A detailed understanding of this mechanism is a necessary step towards the improvement of thermomechanical treatments of iron alloys. Full-field measurements of displacement during heating of high purity iron samples are thoroughly post-processed to track the transformation in situ . They allow a fine characterization of the interaction between local plastic events and microstructure evolutions during the transformation. The deformation of austenite grains bears strong signatures in terms of orientation that can be used to monitor their individual growth in temperature. The parent phase acts as an elastoplastic matrix embedding an inclusion everywhere except at grain boundaries where additional localizations induced by crystal rotations precede the transformation interface.